Comparative Investigation of Fullerene PC71BM and Non-fullerene ITIC-Th Acceptors Blended With P3HT or PBDB-T Donor Polymers for PV Applications - Otieno, Francis; Kotane, Lesias; Airo, Mildred; Erasmus, Rudolph M.; Billing, Caren; Wamwangi, Daniel; Billing, David G. (Frontiers in Energy Research, 2021)
Fundamentally, Organic Solar Cells with bulk-heterojuction active layer is made of at least two types of molecules such that upon absorption of light, generated coloumbically bound exciton can be separated at the donor:acceptor boundaries into free charge carriers. In the past decade, a lot of progress in achieving greater device performance have been made courtesy of the rapid development and evolution of donor and acceptor materials coupled with device engineering. Among the donor materials, regioregular poly(3- hexylthiophene) (P3HT) has produced great performance although is also known for its absorption spectrum that scarcely match the solar emission spectrum compared to PBDB-T that exhibits outstanding absorption coefficient with a deeper-lying highest occupied molecular orbital (HOMO) level. For a long time, efficient acceptors were based on fullerene molecules, which have been found unable to absorb large parts of the sun’s spectrum and have stability issues. In contrast, the recently developed non-fullerene OSCs have a tuneable absorption spectrum and exhibit improved stability. In this work we explore the elemental causes of difference in solar cells device performance of different blend compositions made of fullerene derivative (PC71BM) and non-fullerene (ITIC-Th) when paired with polymer donors P3HT and PBDB-T. We investigated characteristic changes of the optical properties of different blends and related them to device performance. We also studied charge generation where PBDB-T:PC71BM showed the highest maximum exciton generation rate (Gmax) of 3.216 x 10-28 s-1 while P3HT: ITIC-Th gave the lowest (3.216 x 10-28 s-1). Also noted, PC71BM based counterparts gave better charge transfer capabilities as seen from the lower PL quenching and higher charge carrier dissociation plus collection probability P(E,T) derived from a plot of Jph/Jsat ratio under short-circuit conditions against the effective voltages.